Effect of Educative–Supportive Nursing System on Caring Behaviors for Toddler with Pneumonia in Akat Amnuay Hospital, Sakon Nakhon Province - Khodchapim, Orapin (Medical Journal of Sakon Nakhon Hospital, 2024)
This quasi–experimental research aimed to explore the effects of educative–supportive nursing system on caregivers’ care behaviors for children with pneumonia. The subjects were 38 caregivers who cared the children aged 1 to 3 years old with pneumonia admitted in inpatient of Akat Am nuay hospital during February to April 2023. The subjects were divided into two groups; 19 caregivers were in a control group and the others were in an experimental group. Data were collected from February to April, 2023. The purposive sampling was use as a tool for sample selection according to the qualifications. The educative–supportive nursing system was applied to the experimental group. The routine nursing care was given to the control group. The research instruments included 1) the questionnaires for the information of caregivers and their children with pneumonia and 2) the questionnaires for the caregivers’ care behaviors for their children with pneumonia in which the reliability tested by the Cronbach’s alpha coefficient was 0.08. The data were analyzed by using the descriptive statistics; frequency, percentage, means ( ) and standard deviation (S.D.) and the inferential statistics; t–test. The results showed that after the experiment, the caregivers given the educative–supportive nursing system had significantly higher behavior mean score for caring children with pneumonia ( = 83.79, S.D. 4.18) than that of before experiment ( = 73.32, S.D. 4.20) and control group ( = 74.79, S.D. 3.12) who received routine nursing care (p < 0.05 and p < 0.05, respectively). The findings suggested that the educative–supportive nursing system that includes instruction, demonstration guidance, supporting and environmental providing could improve the caregivers’ self–care behaviors for children with pneumonia.